Employment dynamics of married women in Europe - Pierre-Carl Michaud; Konstantinos Tatsiramos (Institute for the Study of Labor (IZA), 2005)
We use eight waves from the European Community Household Panel (1994-2001) to analyze the intertemporal labor supply behavior of married women in six European countries (Netherlands, France, Spain, Italy, Germany and United Kingdom) using dynamic binary choice models with different initial condition solutions and non parametric distributions of unobserved heterogeneity. Results are used to relate cross-country differences in the employment rate to the estimated dynamic regimes. We find that cross-country differences in the employment rate and the persistence of employment transitions of married women are mostly due to composition effects related to education and unobserved characteristics rather than state-dependence effects or the dynamic effect of fertility.
Keywords: C23; C25; D91; J22; 330; intertemporal labor supply; female employment; dynamic binary choice models; initial conditions